Formation of (peace) framework for Madani city concept through empowerment of mosque and waqf land - Rahmat, Azra; Mokhtar, Salbiah; Abdullah, Kamariah; Abdul RahmanAuthor, Norainah; Rahmat, Arina; Kamaruddin, Siti Mazwin (2025)
This study aims to develop a comprehensive strategy framework for empowering mosques and waqf lands under the Madani City Concept, with the goal of revitalizing local towns and fostering prosperous, sustainable communities. Main objectives include identifying the factors to empower mosques and waqf lands in the development of the Madani city concept, analyzing their economic potential, and formulating a strategic framework aligned with MADANI principles, Maqasid Syariah, and national urban policy. Methods employed include systematic literature review, content analysis, and expert interviews involving professionals in urban and Islamic planning. Findings revealed five important elements: Physical, Economy, Administrative, Community, and Environment (PEACE) as the core components. The PEACE model is an innovation to empower mosques and waqf lands in local town development. The proposed PEACE-based framework received positive validation from expert panels and offers a practical guide for future research and implementation in urban planning. This study emphasizes the role of Islamic values in sustainable city development and the optimization of local resources to support community well-being.